The Thinking Strategist : the Power of Strategic Management to Identify, Explore, and Solve Problems. - Cox Edmondson, Vickie (Emerald Publishing Limited, 2018)
Organized in two parts, The Thinking Strategist presents a seven phase strategic management process, helps to clarify terms used by strategists and top leaders, provides theory and practices to empower readers to understand and meet expectations in a business capstone course and in industry, and assumes they are held accountable for results.